EFEK PENGEMBANGAN PERKOTAAN TERHADAP KENAIKAN SUHU UDARA DI WILAYAH DKI JAKARTA URBAN DEVELOPMENT EFFECT TO AIR TEMPERATURE IN JAKARTA AREA - Ali Mas’at (Agromet, 2009)
The purpose of this research is to know the amount of air temperature increase as a negative effect of city development in DKI Jakarta region. The method is to differentiate air temperature in urban areas (Meteorology station in Kemayoran-BMKG) towards sub urban areas (Meteorology station in Halim P.K. and Cengkareng). The result of this research shows that during the last of 28 years, average air temperature has increased 0.17 oC in Jakarta which tends to be 0,8 oC higher than those of sub urban areas.